. - Osabuohien-Irabor, Osarumwense (The European Journal of Applied Economics, 2021)
The goal of this paper is to explore relationship between Twitter andstock liquidity of some large US internet Dot-com companies in thepresence of unknown structural breaks for the period from September2019 to April 2020. Using the Andrews-Ploberger and Andrews-Quandtstructural break models, we identify the major structural breakpointsin the stock liquidity and find that most of these structural changes aresignificantly perceived. When we examined the sub periods as well asthe full sample, Tweets and likes from most numbers of companies werefound not to have links with stock liquidity. These results provide crucialinsight into portfolio strategy to both international and local investors.